2013
DOI: 10.1063/1.4803076
|View full text |Cite
|
Sign up to set email alerts
|

Well controlled multiple resistive switching states in the Al local doped HfO2 resistive random access memory device

Abstract: The resistive switching behaviors in the sandwiched Ti/HfO2/Pt devices with different doping condition were systematically investigated. We show that, comparing with the undoped and the Al layer doped HfO2 devices, significant improvement of switching characteristics is achieved in the Al local doped HfO2 device, including uniformity, reliability, and operation current. As a result, well controlled multiple switching states are obtained in the local doping device by modulating the set current compliance or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…A large effort of experimental works is directed to finding ways of confining the conductive filament in the host oxide insulator, in order to improve the uniformity of resistive switching characteristics. It was found that, aside from embedding nanocrystals and multilayer structures, doping with foreign elements is an easy and effective way to improve resistive switching properties [60][61][62]. Therefore, in order to better understand the ionic conduction properties of the predicted I bam-Hf 2 O 3 phase, we calculated migration barriers for the most important elements, typically used for doping HfO 2 and as electrodes (see Table III).…”
Section: B Functionality With Respect To Forming and Switchingmentioning
confidence: 99%
“…A large effort of experimental works is directed to finding ways of confining the conductive filament in the host oxide insulator, in order to improve the uniformity of resistive switching characteristics. It was found that, aside from embedding nanocrystals and multilayer structures, doping with foreign elements is an easy and effective way to improve resistive switching properties [60][61][62]. Therefore, in order to better understand the ionic conduction properties of the predicted I bam-Hf 2 O 3 phase, we calculated migration barriers for the most important elements, typically used for doping HfO 2 and as electrodes (see Table III).…”
Section: B Functionality With Respect To Forming and Switchingmentioning
confidence: 99%
“…However, compared with high performance metal oxides-based memristors, [64][65][66][67][68] the endurance characteristics and power consumption of the OHPs-based memristors should be improved for further practical memory applications. In addition, some effective methods that have been carried out previously to improve the memristive performances would also applicable in OHPs-based memristors, such as embedding metal clusters, [120][121][122] introducing porous layer, [123][124][125][126] and doping, [127][128][129] and so on.…”
Section: Memristive Characteristics For Memory Applicationsmentioning
confidence: 99%
“…RRAM is one of the most promising candidates for next generation of nonvolatile memory owing to its excellent performance, such as simple structure, low power consumption, fast switching speed, long retention time, and CMOS technology compatibility [4][5][6]. However, the key electrical characteristics of oxide-based RRAM devices still have random dispersion, such as operation voltage and high/low resistance values [7][8][9][10][11][12]. One of the main challenges that hinder RRAM devices from practical device application is exploring effective ways to suppress the fluctuations of key switching parameters, thus improving the resistive switching uniformity.…”
Section: Introductionmentioning
confidence: 99%